Unhabitual presentation of Kimura disease: A case report of gastric localization - Mokni, Wafa; Bdioui, Ahlem; Beltaifa, Dorsaf; Krifa, Marwa; Harrabi, Fethia; Belkacem, Oussama; Hmissa, Sihem; Mokni, Moncef (Biomedicine & Healthcare Research, 2025)
Background: Kimura's disease (KD) is a rare, chronic inflammatory disorder with a benign course and an unclear cause. It primarily affects the head and neck regions. KD is often misdiagnosed due to its resemblance to other benign or malignant diseases, especially when it occurs in uncommon sites. In this report, we present a rare case of KD diagnosed in the stomach. Methods: We report a case of KD localized in the stomach, diagnosed at the Pathology Department of Sahloul University Hospital in Sousse. A 75-year-old female presented with intestinal bleeding. Endoscopy revealed erythematous and hemorrhagic mucosa in the antral and fundic regions of the stomach. A 4 cm antral polyp was identified and subsequently resected. Results: Initial examination of the biopsy specimen concluded with a diagnosis of a low-grade dysplastic polyp. Partial gastrectomy was performed. Histologically, the polyp was bordered by focally ulcerated epithelium without evidence of dysplasia. The axis was edematous, containing clusters of lymphoid cells dispersed within a moderate inflammatory infiltrate rich in eosinophils. Characteristic multinucleated cells with crown-arranged nuclei were observed. The lesion was well vascularized. Immunohistochemistry for CD117, Dog-1, S100 protein, SMA, and ALK was performed to exclude other diagnoses. The results were negative. After multidisciplinary consultation and expert opinion, a diagnosis of KD was established. Conclusion: The stomach is an extremely rare localization for KD. Misdiagnosis can result in unnecessary aggressive treatments, making it essential to distinguish KD from other diseases. While KD generally has a good prognosis with no risk of malignant transformation, its high recurrence rate necessitates careful and ongoing monitoring of affected patients.